Ecological restoration of exposed subsoil conditioned with residues in the Cerrado - Fardin, Flávio Henrique [UNESP]; Maltoni, Kátia Luciene [UNESP]; Boni, Thaís Soto [UNESP]; Faria, Gláucia Amorim [UNESP]; Rezende, Andréia Alves [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
Ecological restoration projects aim to restore native vegetation, and monitoring is an essential step in evaluating the applied technique. The construction of the Ilha Solteira Hydroelectric Power Plant on the Paraná River, between the states of São Paulo and Mato Grosso do Sul (Brazil), in the 1960s, left behind extensive degraded areas, known as borrowed areas and characterized by the removal of the vegetation and superficial soil horizons. The experimental field is located on the Farm of UNESP / Ilha Solteira Campus, in the municipality of Selvíria-MS. Residues were incorporated into the subsoil as conditioners. The residues, aquatic macrophytes (0, 16, and 32 t ha-1) and sugarcane bagasse ash (0, 15, 30 and 45 t ha-1), were combined in 12 treatments and 1080 seedlings (10 different Cerrado tree species) were planted in the study area. The objective of this work was to evaluate the induction of revegetation, established 5 years previously, through the ecological indicators: Soil cover with native vegetation (CSVN); density of native regenerating individuals (DINR) and number of native regenerating species (NENR). Based on the indicators, the results show that the addition of residues and planting of the seedlings were efficient for the ecological recovery of the studied area, with the highest doses of macrophyte yielding the best recovery rates.
Restauração ecológica de subsolo exposto condicionado com resíduos no Cerrado
Keywords: Monitoring; Native regenerating species, Degraded area; Vegetation cover